CREATIVE ABILITIES OF PRIMARY SCHOOL PUPIL`S DEVELOPMENT - Rustamova Davlakhon Toyirjon qizi; Madaminova Dilrabo Khamidullo qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: In this scientific research the main emphasis in the psychological research of creativity is on the intellectual and personal ability of the individual, which encourages independent problem-solving, generates a large number of unique ideas and is the basis for finding their own unique solutions.